A clinicopathologic study of tuberculous epididymo-orchitis in Thailand - Ulan Suankwan (2018)
Tuberculous epididymo-orchitis is an uncommon disease caused by Mycobacterium tuberculosis of the testis and epididymis. We reviewed 25 cases of tuberculous epididymo-orchitis, diagnosed at the Faculty of Medicine Ramathibodi Hospital, Mahidol University between July 2000 and June 2010. The mean age at diagnosis was 54.5 years (range: 30 to 91 years). Cultures from testicular and epididymal tissues were positive for Mycobacterium tuberculosis in 6 cases. The clinical presentations of tuberculous epididymo-orchitis included scrotal mass (80%), scrotal pain (44%), micturition syndrome (8%), urethral discharge (4%), and scrotal fistula (4%). One third of the patients had pulmonary tuberculosis. Four patients (16%) had underlying human immunodeficiency virus infection. Tuberculous epididymo-orchitis should be considered in the patients who present with a scrotal mass. The preoperative differentiation of tuberculous epididymoorchitis from non-tuberculous epididymo-orchitis and testicular tumor is difficult. In patients who have epididymal and testicular lesions, surgical excision provides the diagnosis. Exact histopathologic categorization is important to select appropriate medical therapy.